(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Backgrounds: Direct laryngoscopy and tracheal intubation are noxious stimuli that can provokeundesirable responses in the cardiovascular, respiratory and other physiologic system. These physiologicalchanges are well tolerated by healthy individuals. However, these changes may be detrimental or evenfatal in patients with coronary artery disease, hypertension, cerebrovascular disease, intracranialaneurysm, valvular heart disease.Many pharmacological techniques were introduced and evaluated either in the premedication or duringinduction to attenuate the hemodynamic pressor response to laryngoscopy and tracheal intubation, butresults were controversial. A drug that has analgesic properties, opioid sparing effects, possibly reducesopioid tolerance, relieves anxiety and is not associated with adverse effect would be an attractive adjuvant.Gabamimetic drug like gabapentin have been successfully used as oral premedication to attenuate pressorresponse during airway instrumentation, to decrease the preoperative anxiety and to reduce perioperativefentanyl consumption.In contrast, newer generation Gabamimetic drug pregabalin is effective in preventingneuropathic component of acute nociceptive pain of surgery and is several times more potent thangabapentin. Pregabalin is being used as oral premedicant in some studies but very few comparativestudies with gabapentin is present at time. So, there is a need to study the effectiveness of oral pregabalinin attenuating the hemodynamic response to laryngoscopy and intubation. If pregabalin is established asoral premedicant then it will bring a great benefit to peri-operative period with minimal cost. Objectives: To compare the efficacy of pregabalin and gabapentin in attenuation of laryngoscopy andintubation reflex (HTN & Tachycardia). Methods: This is hospital based randomized double-blind control study. Eighty patients, classified by (ASA)physical status category I-II, were randomized by card method in two groups of 40 patients each. The patientswere randomly allocated to receive oral Pregabalin 150mg (Group A) and Gabapentin 600mg tablet (Group B)1 hour prior to surgery. Before administration of the oral premedication, each patient’s baseline heart rate,systolic and diastolic blood pressure, mean arterial pressure and oxygen saturation were recorded by ananesthesiologist who was not enrolled into the study about the occurrence. In addition, to measure anxietyand sedation Ramsay Sedation Score was completed for each patient. All measurements were repeated beforeinduction. Grade 2 patient was selected. Systolic, diastolic and mean arterial blood pressure (SAP, DAP,MAP) and heart rate (HR), oxygen saturation (Spo2) was recorded after administration of IV anesthetics,immediately after intubation and cuff inflation, and 1, 3, 5 and 10 minutes after intubation. After trachealextubation the patients were monitored for 24 about the occurrence of any side effects, such as nausea,vomiting, dizziness, blurred vision, respiratory insufficiency, confusion and recorded if they were present. Result: Patients characteristics in respect of age, residence, other socio-demographic characteristics,ASA status and type of surgery were similar between the groups. Oral tablet Pregabalin150mg is moreeffective than tablet Gabapentin 600mg, in attenuation of intubation reflex. A single, oral dose of 150 mgof pregabalin premedication seems to be effective in attenuating the hemodynamic response to endotrachealintubation after the first attempt. Conclusion: Pregabalin 150 mg is a better alternative to Gabapentin 600 mg in attenuation of intubationreflex without major side effect. JBSA 2020; 33(2): 98-106